IMPLEMENTASI SMART CITY DI KOTA BANDUNG DALAM MEWUJUDKAN KONSEP SMART GOVERNANCE - Rahdeana Almeyna Kurnia; Kushandajani - -; Laila Kholid Alfirdaus (Journal of Politic and Government Studies, 2023)
This research was conducted to explain the implementation of smart city in Bandung the capital city of West Java, more specifically about the the dimension of smart governance. This study uses a qualitative research methodology with descriptive results and using a data collection techniques through the depth interview with several subjects informant from Bandung City Communication and Information Service as the primary subjects and for the secondary subjects by researched another data to strengthen this research. The theory used in this research is Boyd Cohen’s Smart City concept, which specifically refers to indicators of Smart Governance implementation to measure the successness of Bandung how implemented it. The results of this study indicate that the implementation of Smart Governance in Bandung City is in accordance with some existing indicators, such online service, community participation, infrastructure, and open government. Overall, Bandung has implemented these four indicators and those all have been realized due to supported by Bandung City Government and the cooperation of the local public organizations. Beside, the result also explained how is the impact can be felt for the public